Violences à caractère sexuel: Les actes « graves » de Samuel Archibald - Perron, Louis-Samuel (La Presse, 2022)
L’écrivain réputé Samuel Archibald a profité de son statut de professeur de littérature pour avoir des relations sexuelles avec deux étudiantes sous son autorité, conclut une enquête indépendante commandée par l’Université du Québec à Montréal (UQAM). Une de ces femmes l’accuse même de l’avoir étranglée lors d’une relation sexuelle non consentie. Des actes « graves » et « hostiles » qui ont mené à son départ en catimini de l’UQAM l’an dernier.
Keywords: Bibliographie; Irina; Nettoyer

Creative Industries in Canada - Thompson, Cheryl; Campbell, Miranda (Canadian Scholars, 2022)
Keywords: Cultural industries.; Irina

La quatrième vague du féminisme : quel impact sur le champ littéraire ? - Mairesse, Lise (Université catholique de Louvain, 2022)
Keywords: Bibliographie; Irina; Nettoyer

Review: Cooperative Gaming: Diversity in the Games Industry and How to Cultivate Inclusion - Hanussek, Benjamin (Press Start, 2022)
Review: Cooperative Gaming: Diversity in the Games Industry and How to Cultivate Inclusion, by Alayna Cole and Jessica Zammit. 2020. CRC Press. xv + 95 pp.
Number: 2
Keywords: Irina; diversity; game industry; game studies; inclusion

Exploring Vicarious Liability to Remedy the #E-Too Movement - Hewson, Eloise (York Law Review, 2022)
The esports, or competitive video gaming, industry is an exciting area of economic and cultural growth. Gaming can facilitate interpersonal connection, shared problem-solving, and creativity. Players may purchase a game, watch a streamer play it online, join an online gaming community, attend a tournament, compete professionally, or find employment in game development or a related field. The gaming industry generates enormous economic value and employs tens of thousands of people in the UK alone. However, the esports sector does not extend its benefits equally. Women are regularly verbally harassed in video games, countless women have been groped at esports events, women have been raped by professional players, underage fans have been groomed. Abuse is endemic to online gaming communities.
Keywords: Bibliographie; Irina; Nettoyer

Working with “monstrous men”: ambivalent sexism in the Bombay film industry - Sanchez Lozoya, Zeltzyn Rubi (Feminist Media Studies, 2022)
In India, the 2012 Delhi gang rape case catalyzed protests for women’s rights, particularly in regard to their safety. These demands were rekindled with vigor anew with the eruption of the #MeToo movement. In the Indian film industry, the most visible change appeared in the gradual increase of films with womenleads. But behind the scenes, there has been comparatively less change in female representation. Currently, approximately less than 10% of film directors in India are women. Considering the impor tance of having stories about women being made by women, in this article I examine the factors that hinder women’s entrance and tenure in the Mumbai film industry. I argue that a composite of concerns, including but not limited to reputability and personal security, thwarts women’s progress in the industry. I base my con clusions on interviews with women and men working in the film industry, conducted in Mumbai in 2017. I use the framework of the Ambivalent Sexism Index developed by psychologists Glick and Fiske in 1996, and revised in 2013, (1996, 2001, 2013) to examine my interviewees’ encounters with hostile and benevolent sexism. This article complicates our understanding of the reasons that limit the work of women beyond explanations of overt discrimination.
Keywords: Irina

Que fait #MeToo à la littérature ? - Zenetti, Marie-Jeanne (Revue critique de fixxion française contemporaine, 2022)
Que fait #MeToo fait à la lecture, à la critique et à l’enseignement des textes littéraires ? Le mouvement #MeToo a contribué à une large prise de conscience quant aux enjeux linguistiques liés aux violences sexuelles et sexistes : lutter contre de ces violences suppose d’abord de nommer un viol un viol. Mais une telle exigence de désambiguïsation peut entrer en contradiction avec la complexité interprétative valorisée dans le cadre de la lecture littéraire. Elle présenterait par ailleurs le risque d'inviter à lire des textes éloignés de nous dans le temps et l’espace en les évaluant à l’aune de notions et d’une morale contemporaines jugées anachroniques. Prolongeant les réflexions récentes de Gisèle Sapiro (Peut-on dissocier l’œuvre de l’auteur ?) et d’Hélène Merlin-Kajman (La littérature à l’ère de MeToo), cet article étudie la réception du récit de Vanessa Springora, Le consentement (2020). En interrogeant la polarisation des discours critiques et théoriques entre une lecture “féministe” et une lecture “littéraire” parfois présentées comme incompatibles, il pose la question du lien possible entre violences sexuelles et pratiques interprétatives. Il théorise une pratique de lecture soucieuse de contextualiser l’usage des modèles interprétatifs mobilisés dans l’analyse littéraire et de les critiquer en interrogeant les rapports de pouvoir qu’ils dissimulent. Il défend ainsi l’hypothèse que le mouvement #MeToo invite les littéraires à réévaluer leurs pratiques et leurs paradigmes de lecture en fonction de ce qu’ils rendent possible.
Number: 24 Publisher: Ghent University
Keywords: #metoo; Irina; consentement; lecture féministe; lecture littéraire; violences sexuelles

Let Her Play: A report on gender-based violence in video games - Mettler, Kirsten (Embodied: The Stanford Undergraduate Journal of Feminist, Gender, and Sexuality Studies, 2022)
Globally, video games are a $152 billion industry, and approximately 3.1 billion people, or 40% of the population, are players (Ingersoll & Anti-Defamation League, 2019, Price, 2020). Gaming is a huge industry, and it’s only getting bigger. Unfortunately, women and other historically marginalized groups often face staggering levels of harassment and violence in these communities. This report aims to explore the issue of gender-based violence in video games by analyzing contributing factors and proposing gaming company interventions.
Number: 1
Keywords: Bibliographie; Irina; Nettoyer; esports

Understanding Sexual Harassment in the #MeToo Era - Julios, Christina (Sexual Harassment in the UK Parliament: Lessons from the #MeToo Era, 2022)
This chapter provides a contextual account of the rise of #MeToo as an global gender-equality campaign supporting those affected by sexual transgressions. Originally articulated by African-American civil rights activist Tarana Burke in 2006, the slogan ‘me too’ was meant as a rallying cry to support young minority ethic survivors of sexual abuse. Years later, social media would turn Burke’s motto into a byword for the global #MeToo movement. The chapter chronicles the events surrounding #MeToo’s inception, including Hollywood producer Harvey Weinstein’s sexual exploitation scandal in 2017, and The New York Times and The New Yorker exposés of his serial offending within the film industry. It also examines the narratives of countless survivors and #MeToo campaigners, including high-profile cases such as those of Rose McGowan, Alyssa Milano, Mimi Haleyi, Jessica Mann and Zelda Perkins. The chapter then critically considers the growth and international significance of #MeToo as well as its inherent shortcomings.
Keywords: #MeToo; Farrow; Harvey Weinstein; Irina; Kantor and Twohey; Rose McGowan

Women actors, insecure work, and everyday sexism in the Canadian screen industry - Liinamaa, Saara; Rogers, Malia (Feminist Media Studies, 2022)
Acting, especially in the screen arts industry, is a job where women are subjected to pronounced and widely accepted socio-cultural aesthetic ideals within an industry that has become renowned for its tolerance for and justifications of sexism and sexualized violence. However, there is a limited amount of scholarship that examines actors and acting from a work and employment perspective. Drawing on the literature on work insecurity and gender inequities in cultural work, this article examines the screen industry from the perspective of women actors in a semi-peripheral location in Canada. This is a cohort that has managed to remain in the industry, despite high levels of attrition. Drawing on in-depth semi-structured interviews, our participants identify a range of strategies they employ (toughness, silence, humour, refusal, creative resistance) to respond to workplace sexism and gender-based constraints as they try to balance their creative agency with career sustainability. Participants emphasized that finding multiple outlets for realizing creative agency is crucial to counteracting everyday sexism and remaining in the industry.
Publisher: Routledge _eprint: https://doi.org/10.1080/14680777.2020.1759114
Keywords: Bibliographie; Irina; Nettoyer; Screen industry; everyday sexism; gender and cultural work; women actors and acting

Sex and safety on set: intimacy coordinators in television drama and film in the VOD and post-Weinstein era - Sørensen, Inge Ejbye (Feminist Media Studies, 2022)
This article examines the work of intimacy coordinators on television drama and film sets and the rise of this new role in the screen industry from a policy and production studies perspective. Since HBO made the employment of an intimacy coordinator mandatory on all productions with scenes of sex, nudity, and physical intimacy in 2018, intimacy coordination has become an industry standard and expectation. Through interviews and analysis of production practices, this article explores how intimacy coordinators change and challenge established production practices on and off set and interrogates the reasons behind the emergence of this role in the screen industry. It situates intimacy coordination in the context of recent industry policies and initiatives that promote equality and diversity, and counter harassment and abuse in the post-Weinstein era. It analyses this role on relation to changing production and distribution models and regimes in the era of VOD portals. The article argues that intimacy coordination is not only a catalyst for reforming practices on set, but a way for the screen industry to negotiate contemporary and historic concerns about sexual harassment and abuse, comply with recent policy and funding requirements, and a mechanism for mitigating economic and reputational risk to productions.
Publisher: Routledge _eprint: https://doi.org/10.1080/14680777.2021.1886141
Keywords: #MeToo; Intimacy Coordination; Irina; Prévention; VOD; equality; screen industries

The impact of #MeToo in the South African film and television industry, within a historical framework - Majiba, Ntsika (Université de l'Afrique du Sud, 2022)
The study is a history project and is concerned with tracking the impact of #MeToo in the South African Film and Television industry in South Africa. Its main premise were the findings made public by a South African organization, Sisters Working in Film and Television (SWIFT) in 2017, that found that sexual harassment in the television and film industry was not just a norm but a crisis. The core focus of the study was on the development and impact of the #MeToo movement, which entailed investigating the manner in which women reacted to the hashtag (#MeToo), the reaction of their male counterparts, as well as the reaction and actions taken by the various bodies, institutions and organisations in the Film and Television industry, which included; broadcasters and production houses alike. This study begins by giving a concise background of the movement by firstly, historicising various female-led movements and comparing and contrasting them with the rise of digital movements or digital activism. The historicisation involves a brief comparison of past and present women-led activism, as well as a brief review of other hashtags like #AmINext and #Enough, on which #MeToo has had an influence. It goes on to investigate the development of #MeToo movement and to discuss the responses of the industry and individuals to the movement. The study embarked on a data collection quest by interviewing eleven female television and film practitioners in South Africa. Their ages ranged from 20 to 55. The findings of the research revealed that female practitioners were still being harassed post #MeToo, although subtly. The lack of unity amongst women in the sector was cited as one of the reasons behind the ongoing harassment. Gender parity and equity was also still lacking in the South African television and film industry. This study emerged in the midst of activism and scholarship seeking to unravel the norms of South African sexual harassment and rape culture against women. Thus, the study focused on the changes and transformations brought about by the hashtag within the industry. With South Africa’s historical background and the current circumstances around Gender Based Violence (GBV), this study was concerned with tracking whether or not digital activism had in some way been able to aid change and transformation. In particular, this study looked at the impact of the MeToo phenomenon on the women in the industry, the extent to which it empowered them, what they began to say and how they began to act. The study also explored South Africa’s ‘rape culture’ as South Africa has been proclaimed the ‘worlds rape capital’. It reflected on the colonial rule as the perpetuation of patriarchy and male entitlement over female bodies. Patriarchy in the industry was also confirmed by the findings and through data analysis, as one of the key factors in the emergence of #MeToo in South Africa, and in the utilisation of the hashtag by women in the sector to speak up against sexual harassment.
Accepted: 2023-02-20T11:59:11Z
Keywords: Bibliographie; Irina; Nettoyer